African languages in education. Orality as a way forward - (:unkn) unknown (My University, 2014)
In Africa, the use of African languages in education is often reduced to a mere change of medium. This cannot work, as past experiences have amply shown and this rationale is even reinforced by globalization. The use of African languages in school must be buttressed on their inner strength, viz., local lore and orality. We suggest this can be achieved through a revamped and rebased primary schooling relying on the implication of community members. This in turn could alleviate some of the shortcomings formal education presently experiences. Such a change of framework is urgent, particularly in urban areas, to ensure transmission of linguistic and cultural legacies.
Keywords: African Research